Combined effects of hypoxia or elevated temperature and Deepwater Horizon crude oil exposure on juvenile mahi-mahi swimming performance. (August 2018) - Mager, Edward M.; Pasparakis, Christina; Stieglitz, John D.; Hoenig, Ronald; Morris, Jeffrey M.; Benetti, Daniel D.; Grosell, Martin
Abstract: This study examined potential interactive effects of co-exposure t o Deepwater Horizon ( DWH ) crude oil (∼30 μg L −1 ΣPAHs) for 24 h and either hypoxia (2.5 mg O2 L −1 ; 40% O2 saturation) or elevated temperature (30 °C) on the swimming performance of juvenile mahi-mahi ( Coryphaena hippurus ). Additionally, effects of shorter duration exposures to equal or higher doses of oil alone either prior to swimming or during the actual swim trial itself were examined. Only exposure to hypoxia alone or combined with crude oil elicited significant decreases in critical swimming speed ( U crit ) and to a similar extent (∼20%). In contrast, results indicate that elevated temperature might ameliorate some effects of oil exposure on swimming performance and that effects of shorter duration exposures are either reduced or delayed. Highlights: Hypoxia alone or combined with 2% HEWAF elicited similar decreases in U crit . Elevated temperature alone or combined with 2% HEWAF did not affect U crit . Shorter 12 h exposure to 4% HEWAF did not affect U crit . 20% HEWAF exposure during swim trials did not affect U crit .